Morphological and multigene phylogenetic analyses reveal two new nematode-trapping fungi (Arthrobotrys, Orbiliaceae) from Yunnan, China - Yang, Yao-Quan; Zhang, Fa; Li, Zheng-Qiang; Zhou, Fa-Ping; Yang, Xiao-Yan; Xiao, Wen (Phytotaxa, 2023)
During the investigation of nematode-trapping fungi in Yunnan Province, four strains were isolated from the soil collected in Nujiang City, Yunnan Province, China and were identified as two new Arthrobotrys (Orbiliaceae) species based on morphology and multigene (ITS, EF1-α, and RPB2) phylogenetic analysis. Arthrobotrys gongshanensis is characterized by conidiophores producing 1–5 short denticles near the apex, bearing a single conidium on each denticle and obovoid to fusiform, 1–4-septate conidia. Arthrobotrys luzhangensis is characteristics by its obovoid to fusiform, 1–4-septate macroconidia, and clavate or obovoid, aseptate microconidia. These two new species both capture nematodes using adhesive networks. The multigene phylogenetic analyses further confirmed the taxonomic positions of these two new species within Arthrobotrys. This paper described them with illustrations and compared them with similar taxa.